Serpentine (Floating) Ice Channels and their Interaction with Riverbed Permafrost in the Lena River Delta, Russia - Juhls, Bennet; Antonova, Sofia; Angelopoulos, Michael; Bobrov, Nikita; Grigoriev, Mikhail; Langer, Moritz; Maksimov, Georgii; Miesner, Frederieke; Overduin, Pier Paul (Frontiers in Earth Science, 2021)
Arctic deltas and their river channels are characterized by three components of the cryosphere: snow, river ice, and permafrost, making them especially sensitive to ongoing climate change. Thinning river ice and rising river water temperatures may affect the thermal state of permafrost beneath the riverbed, with consequences for delta hydrology, erosion, and sediment transport. In this study, we use optical and radar remote sensing to map ice frozen to the riverbed (bedfast ice) versus ice, resting on top of the unfrozen water layer (floating or so-called serpentine ice) within the Arctic’s largest delta, the Lena River Delta. The optical data is used to differentiate elevated floating ice from bedfast ice, which is flooded ice during the spring melt, while radar data is used to differentiate floating from bedfast ice during the winter months. We use numerical modelling and geophysical field surveys to investigate the temperature field and sediment properties beneath the riverbed. Our results show that the serpentine ice identified with both types of remote sensing spatially coincides with the location of thawed riverbed sediment observed with in situ geoelectrical measurements and as simulated with the thermal model. Besides an insight into sub-river thermal properties, our study shows the potential of remote sensing for identifying river channels with active sub-ice flow during winter versus channels, presumably disconnected for winter water flow. Furthermore, our results provide viable information for the summer navigation for shallow-draught vessels.